PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN TINGKAT DASAR DENGAN MEMANFAATKAN LIMBAH SAMPAH DI SEKOLAH - Armanila Nila; Dirja Hasibuan; Hasnah Siahaan; Abdul Halim; Mesran; Syariah Hafidzhoh (CV. Multi Kreasi Media, 2022)
Teaching and learning activities in Raudhatul Athfal throughout the Hamparan Perak sub-district are still limited in the use of learning media. Therefore, the purpose of implementing community service activities is to provide skills for teachers in the manufacture and use of learning media by utilizing school waste, where the participants or targets are raudhatul Athfal teachers, Hamparan Perak District, consisting of 19 teachers who participate in mentoring and are the delegates from 6 Kindergartens in Hamparan Perak District, through training and mentoring methods with four stages, namely planning, implementation, mentoring and evaluation. It can be concluded that the learning media by utilizing waste waste developed in the service program turned out to be an alternative for teachers in delivering learning material in a fun way.